2000
DOI: 10.1136/bjo.84.8.848
|View full text |Cite
|
Sign up to set email alerts
|

Audit of outcome of an extracapsular cataract extraction and posterior chamber intraocular lens training course

Abstract: Background-A training course for cataract surgery with intraocular lens implantation was organised in April 1997 at the National Eye Centre, Kaduna, Nigeria. Operations were performed by six Nigerian consultant ophthalmologists under the supervision of two surgeons from Aravind Eye Hospital, India. Methods-A total of 175 eyes with uncomplicated cataracts were operated on after careful selection. All but six patients had extracapsular cataract extraction with posterior chamber intraocular lens insertion during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
3
4
1
Order By: Relevance
“…Surgical complications were more common among doctors who are undertrained, as indicated in earlier reports. [6][7][8] Similar findings have been reported from training centers that have trainees with different skill levels. [6][7][8] Visual rehabilitation is difficult in cases of aphakia.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Surgical complications were more common among doctors who are undertrained, as indicated in earlier reports. [6][7][8] Similar findings have been reported from training centers that have trainees with different skill levels. [6][7][8] Visual rehabilitation is difficult in cases of aphakia.…”
Section: Resultssupporting
confidence: 86%
“…[6][7][8] Similar findings have been reported from training centers that have trainees with different skill levels. [6][7][8] Visual rehabilitation is difficult in cases of aphakia. Long-term contact lens use may be attempted, but this is not a practical solution, as it is associated with numerous problems.…”
Section: Resultssupporting
confidence: 86%
“…[ 6 ] By contrast, studies conducted in other parts of Nigeria in Ago Iwoye, Kaduna, Orlu, and Port Harcourt showed slight male predominance. [ 7 8 9 10 ] A hospital-based study conducted in Auckland, New Zealand, and Lahan district of Nepal, respectively, also reported female predominance in uptake of cataract surgery. [ 11 12 ] This higher number of females in our study may be due to increasing awareness about cataract surgical services in our facility from community health talks, free eye camps conducted at various times or from increased financial support from the friends of Hospital or other philanthropists.…”
Section: Discussionmentioning
confidence: 99%
“…20 Poor visual outcomes following extracapsular cataract extraction (ECCE) with IOL have been reported in 9.7-15.5% of operated eyes in multiple hospital-based reports from Nigeria. [21][22][23] Another study from Gondar (northwest Ethiopia) showed good, borderline and poor visual outcomes in 26.6%, 28.9% and 44.5% of operated eyes, respectively. 24 That we saw relatively better outcomes in our study might be due to the fact that the majority of surgeries were performed by senior ophthalmologists and the final vision assessment being at 6-8 weeks (versus 1-4 weeks for two-thirds of patients in the Gondar study).…”
mentioning
confidence: 97%